2023
DOI: 10.1039/d2lc01008a
|View full text |Cite
|
Sign up to set email alerts
|

A super water-resistant MXene sponge flexible sensor for bifunctional sensing of physical and chemical stimuli

Abstract: Flexible wearable sensors with multifunctional features have attracted great interest in various applications such as disease diagnosis, environmental detection and healthcare monitoring. However, it remains a challenge to achieve...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Therefore, multifunctional sensors that can simultaneously detect pressure/strain and humidity have also attracted people’s attention. Most functional nanomaterials such as MXene, carbon nanomaterials, etc., and some water-sensitive polymers such as hydrophilic polymers (polyacrylamide, poly­(vinyl alcohol), etc. ) exhibit humidity sensitivity and can detect humidity using changes in resistance or capacitance caused by changes in humidity .…”
Section: Dual-modal Flexible Sensorsmentioning
confidence: 99%
“…Therefore, multifunctional sensors that can simultaneously detect pressure/strain and humidity have also attracted people’s attention. Most functional nanomaterials such as MXene, carbon nanomaterials, etc., and some water-sensitive polymers such as hydrophilic polymers (polyacrylamide, poly­(vinyl alcohol), etc. ) exhibit humidity sensitivity and can detect humidity using changes in resistance or capacitance caused by changes in humidity .…”
Section: Dual-modal Flexible Sensorsmentioning
confidence: 99%
“…Similarly, Li et al reported a piezoresistive pressure sensor based on an in situ grown silver/gold nanostructure on a melamine sponge ( Figure A), which showed a high sensitivity of 12 kPa –1 , a small response time of 85 ms, and excellent durability that could sustain over 2 × 10 4 cycles of compression. Xu et al reported the dip coating of MXene on a melamine sponge for the development of a porous sensor . Based on the response of MXene and the porous structure of the melamine sponge, the resistance of the MXene-coated melamine sponge exhibited a fast response and long-term stability, demonstrating its application in respiratory monitoring.…”
Section: Strategies To Realize Permeable Electronicsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Desirable flexible multifunctional DOI: 10.1002/adsr.202300048 sensors are capable of detecting and differentiating between physical stimuli (e.g., strain and stress) and chemical stimuli (e.g., chemical gas molecules). [7][8][9][10][11][12] And the flexible sensors, generally, are composed of conductive materials and flexible substrates. For the conductive materials, different kinds of polymers, such as polyaniline (PANI), polypyrrole (PPy), or poly (3,4-ethylene dioxythiophene), are the alternatives to expensive inorganic materials and carbon materials.…”
Section: Introductionmentioning
confidence: 99%